The challenge of stress induction in serious games, considering gameplay - Gonçalves, Thiago da Silva; Silva-Calpa, Greis Francy M.; Porcino, Thiago Malheiros; e Almeida, Raphael de Souza; Raposo, Alberto Barbosa (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Stress induction is crucial for training personnel in high-pressure situations, such as military, first responders, and healthcare professionals. The ability to perform effectively under stress is a critical skill for these professionals, as their decisions can have significant consequences. One of the most effective methods for inducing stress in training scenarios is through the use of virtual environments. Virtual Reality (VR) and Augmented Reality (AR) technologies have become increasingly sophisticated, allowing for the creation of highly realistic and immersive training environments. These technologies can simulate a wide range of scenarios, from battlefield conditions for military personnel to emergency response situations for first responders and complex surgical procedures for healthcare professionals. This type of training aims to prepare individuals to respond effectively in real-life scenarios, enhancing resilience and decision-making abilities under stress. Measuring stress levels during these trainings is essential to assess program effectiveness and adjust methodologies as needed. By monitoring physiological and psychological stress indicators, such as heart rate variability, cortisol levels, and self-reported stress scales, trainers can determine if the scenarios are inducing the desired level of stress. This measurement ensures that participants are genuinely engaged in the training, allowing for real-time adjustments to the intensity and nature of the scenarios to maximize the training benefits. Additionally, it helps in verifying that the participant is fully immersed and responding realistically to the simulated high-pressure environment, ensuring the training’s relevance and effectiveness. Therefore, through a Systematic Literature Review, this study investigated the best biomarkers and their combinations and protocols used, aiming to determine the most effective way to measure stress induction in training to improve their efficiency.